2000
DOI: 10.1111/j.1365-2672.2000.tb05343.x
|View full text |Cite
|
Sign up to set email alerts
|

The fate ofEscherichia coliandE. coliO157 in cattle slurry after application to land

Abstract: SUMMARY The fate of both faecal Escherichia coli and E. coli O157 in slurry following application to arable and grass plots on a clay loam soil was studied. Slurry (5% dry matter) containing 53 × 104 ml−1 E. coli and 30 E. coli O157 100 ml−1 was spread in early March. Initially, almost all E. coli were retained in the upper layers of the soil. Escherichia coli numbers steadily declined to less than 1% of those applied by day 29, and E. coli O157 were only detected in the soil and on the grass for the first wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
94
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(107 citation statements)
references
References 14 publications
10
94
1
Order By: Relevance
“…However, once faeces have become mixed with soil, ingestion is more likely. The model developed in this paper, assumes that the faeces is mixed homogeneously in the top 1 cm of soil which is in broad agreement with the experimental results (Fenlon et al, 2000;Strachan et al, 2001).…”
Section: Concentration On the Pasturesupporting
confidence: 74%
See 2 more Smart Citations
“…However, once faeces have become mixed with soil, ingestion is more likely. The model developed in this paper, assumes that the faeces is mixed homogeneously in the top 1 cm of soil which is in broad agreement with the experimental results (Fenlon et al, 2000;Strachan et al, 2001).…”
Section: Concentration On the Pasturesupporting
confidence: 74%
“…Since the proportion of organisms with this long survival factor is low ( < 5%, Ogden et al, 2001b), they have been ignored in the current study as the probability of human infection arising from their direct ingestion is thought to be small. Soil type may also need to be considered as Fenlon et al (2000) showed decay to be faster in sandy soils compared with clay and loam.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bacteria can survive longer in cold soils and fine textured soils (Fenlon et al, 2000). In cold soils (o5 1C) E. coli can survive for up to 100 days.…”
Section: Persistence Of Pathogens In the Environmentmentioning
confidence: 99%
“…E. co/zO157:H7 survives well in the environment with recovery for up to 70 days reported from bovine faeces (Wang et al 1996) and for 63 days from pasture (Hutchison et al 2005). It has been reported that E. coliO157:H7 can be leached from a range of soil types after rainfall (Fenlon et al 2000;Gagliardi & Karns 2000). Islam et al (2005) recovered^, coli O157:H7 from carrots and onions harvested from plots that had been sown following application of contaminated manure or irrigation water.…”
Section: Introductionmentioning
confidence: 99%